Pengaruh Gula Aren (Arenga Pinnata) Terhadap Endurance Pada Atlet Porprov Pencak Silat - Riswanto, A Heri; Islamuddin, Irma; Jalil, Rasyidah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
This research aim is to determine wheter there is a effect of palm sugar (arenga pinnata) on endurance in porprov martial art athletes in Luwu Districts. This type of research is an experimental study with one independent variable and one dependent variable. The populations in this study were all athletes from the porprov martial art competition in Luwu Districts. A sample of 13 people was obtained by determining the all sampling sample. Based on the result of data analysis, it can be conclued that the result of the pretest bleeb test obtained an average value of 40,169, posttest bleeb test obtaine an average value of 42,192, the pretest of the initial heart rate test obtained an average value of 84, 615, the posttest of the initial heart rate test of the posttest obtained an average value of 86,308, the pretest exercise heart rate test obtained an average value of 146,000, the posttest exercise heart rate test obtained an average value of 149,692. It can be include that there is a significant effect of palm sugar (arenga pinnata) on endurance in porprov martial art athletes in Luwu Districts.